2021
DOI: 10.3390/ijms22168855
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency, Osteoporosis and Effect on Autoimmune Diseases and Hematopoiesis: A Review

Abstract: Vitamin D (VD) is essential for bone homeostasis, but it is also involved in pleiotropic effects on various organs and tissues. In adults, VD deficiency can cause or exacerbate osteoporosis and induce osteomalacia. However, every tissue and cell in the body has a VD receptor, including the brain, heart, stomach, pancreas, skin, gonads, and immune cells, and a deficiency may modify the function of these organs. Thus, the wide-ranging actions of VD help to explain why a reduction in VD amount has been correlated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 227 publications
(237 reference statements)
0
32
0
1
Order By: Relevance
“…Calcitriol signalling is crucial in bone metabolism as it is involved in calcium absorption, parathormone secretion and, therefore, bone resorption and cellular differentiation. Vitamin D deficiency has been associated with bone metabolism alterations [35][36][37]. Therefore, vitamin D intake as a preventive nutritional treatment of osteoporosis plays an important role in improving health status [38,39], but the efficacy of supplementation varies widely between subjects [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Calcitriol signalling is crucial in bone metabolism as it is involved in calcium absorption, parathormone secretion and, therefore, bone resorption and cellular differentiation. Vitamin D deficiency has been associated with bone metabolism alterations [35][36][37]. Therefore, vitamin D intake as a preventive nutritional treatment of osteoporosis plays an important role in improving health status [38,39], but the efficacy of supplementation varies widely between subjects [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, also Th2-cells [338] and Treg-cells are induced [339], while Th17-mediated autoimmunity can be ameliorated by 1,25-dihydroxyvitamin D 3 [340]. As chronic diseases often go along with vitamin D deficiency [341] and low vitamin D levels are correlated with higher immune activation markers like neopterin, e.g., in CAD patients [342], vitamin D supplementation of patients might be very effective to downregulate underlying inflammatory processes.…”
Section: Nutrition In the Treatment Of Anemia Of Inflammationmentioning
confidence: 99%
“…Patients requiring palliative care are at greater risk for vitamin D deficiency/insufficiency as a result of less exposure to sunlight, lower oral intake and a decreased ability to absorb dietary vitamin D (19,22). In addition, studies mentioned in the literature have found a relationship between vitamin 25(OH)D and extremity functions, muscle strength and physical activity and it has been determined that vitamin D deficiency may increase the risk of falling in the elderly (10,13). In a cross-sectional study conducted on 30 palliative cancer patients in Spain, a statistically significant relationship was found between 25-OHD vitamin levels and the general quality of life (23).…”
Section: Discussionmentioning
confidence: 99%
“…Its clinical effects have been documented in many studies. VDD has been associated with cardiovascular diseases, increased risk of fractures, dyslipidemia, increased inflammation, glucose metabolism disorders, weight gain, infectious diseases, multiple sclerosis, mood disorders, cognitive dysfunction, impaired physical functions and mortality rates connected to all types of reasons (10).…”
mentioning
confidence: 99%